Eyes on Phact: unraveling a Be star and its disk - Rubio, Amanda Caveagna (2019)
Disks are a common feature in astrophysical systems. They are present in young stellar objects, cataclysmic variables, and even active galactic nuclei. Many of these disks can be well described by the $\\alpha$-disk formulation, that assumes the build up of the disk is regulated by the viscosity of the material, described by a parameter called simply alpha. All disks in the systems cited are accretion disks: the matter on the disk is spiralling towards the central object, be it a star or a compact object such as a black hole. There is, however, a very particular case where the disk is actually decreting, built from matter expelled from the central object: Be stars. Be stars are fast rotating B type stars that, through the elusive Be phenomenon, eject mass into orbit, forming a viscous Keplerian disk. The model that best describes these objects is an alpha-disk modification, the Viscous Decretion Disk model (VDD), where viscosity is the main force acting on the disk once matter enters orbit. The VDD has been successfully tested by several multi-technique studies of Be stars, and is now cemented as the paradigm for these objects. With the robust framework of the VDD as bedrock, we are now able to tackle the issue of determining the fundamental parameters of these stars in novel ways using modern techniques, such as Bayesian-Monte Carlo Markov chain inference. In this work, we combine Bayesian-MCMC techniques with state-of-the-art radiative transfer model grid BeAtlas to infer the fundamental parameters of the Be stars $\\alpha$ Col, for which we were able to determine stellar, geometric and disk parameters using photometry, polarimetry and UV spectroscopy data. We find that alpha Col is a ~4.66 Msol star, very evolved, with a rotation rate of 0.74. The system is seen at an inclination of approximately 40º. The disk is tenuous and has a density exponent of 2.5, steeper than what is expected by VDD theory for a stable Be star such as alpha Col, a result that agrees with a trend of n < 3.5 for Be stars in recent studies. The disk is also truncated at 20 Req, indicating the presence of a previous unseen, close binary companion.